Tears of a tiger - Draper, Sharon M. (Sharon Mills) (New York, NY : Aladdin Paperbacks, 1996)
The death of high school basketball star Rob Washington in an automobile accident affects the lives of his close friend Andy, who was driving the car, and many others in the school.
Notable/Best Books (A.L.A.).
Wilson's Junior High School.
Wilson's Senior High School.
6.5
Young Adult
Keywords: African Americans -- Fiction; Death -- Fiction; High schools -- Fiction; Schools -- Fiction; African Americans -- Fiction; Death -- Fiction; High schools -- Fiction; School stories